Urban pressure around areas of natural heritage. Cenas tīrelis - Ziemeļniece, Aija; Vanaga, Emīlija (Landscape Architecture and Art, 2023)
The study looks at the perimeter or ring encroachment of anthropogenic pressures around areas of natural substrate or marshland. The anthropogenic load, the intensity of which began with the invasion of the Soviet-era economic policy and the wave of migrants bringing large numbers of migrant workers to Latvia in the 1960s-80s, brought with it an alien understanding of living space, exaggerations of the scale of development, a distorted understanding of spatial harmony and equilibrium. Rapid settlement construction, the establishment of drainage networks, the pace of collectivisation and agro-technology, and logging began. These are things that today are being increasingly controlled in the spatial plans of municipalities. To maintain the sustainable development of the natural base, it is necessary to look for ways of bringing residential areas closer to it, without reducing the ecological status. The settlements of the 3 districts of the Tīrelis of Cena are examined in more detail, where the 19th–21st centuries are described. transformation processes.